Screening of microalgae for integral biogas slurry nutrient removal and biogas upgrading by different microalgae cultivation technology - Xue Wang (Nature Portfolio, 2017)
Abstract The microalgae-based technology has been developed to reduce biogas slurry nutrients and upgrade biogas simultaneously. In this work, five microalgal strains named Chlorella vulgaris, Scenedesmus obliquus, Selenastrum capricornutum, Nitzschia palea, and Anabaena spiroides under mono- and co-cultivation were used for biogas upgrading. Optimum biogas slurry nutrient reduction could be achieved by co-cultivating microalgae (Chlorella vulgaris, Scenedesmus obliquus, and Nitzschia palea) with fungi using the pelletization technology. In addition, the effects of different ratio of mixed LED light wavelengths applying mixed light-emitting diode during algae strains and fungi co-cultivation on CO2 and biogas slurry nutrient removal efficiency were also investigated. The results showed that the COD (chemical oxygen demand), TN (total nitrogen), and TP (total phosphorus) removal efficiency were 85.82 ± 5.37%, 83.31 ± 4.72%, and 84.26 ± 5.58%, respectively at red: blue = 5:5 under the co-cultivation of S. obliquus and fungi. In terms of biogas upgrading, CH4 contents were higher than 90% (v/v) for all strains, except the co-cultivation with S. obliquus and fungi at red: blue = 3:7. The results indicated that co-cultivation of microalgae with fungi under mixed light wavelengths treatments was most successful in nutrient removal from wastewater and biogas upgrading.